Effectiveness of ABA Therapy for Children with Special Needs of Autism: A Study of Psycholinguistics View - Siti Ithriyah (Universitas Cokroaminoto Palopo, 2018)
The background of this study is the recognition of an expert consultant psychiatrist named dr. Suzy Yusna SpKJ, who stated in our interview that based on the experience of practice before the 1990's the number of patients who were diagnosed as a child with autistic disorder in a year is only about five people. However, at this time of day can be diagnosed, three new patients. This shows a significant increase in autism. This study aims to describe (1) the effectiveness of Applied Behavioral Analysis (ABA) therapy model to increase autistic children's language; and (2) language development of children with autism after acquiring learning methods ABA therapy. This research method is descriptive research. The study takes its source data from children with special needs at Rumah Autis Bogor. Five children were selected as the research participants. We conclude that Lovaas’ ABA method to prove the effectiveness of these therapies through phases and methods. Therapists who are experts in this field also helped determine the success in measuring the response level of language learning for children with autism. Thus, effective ABA therapy model applied in improving the language of children with autism. Before the ABA method is applied, the average child's ability to speak to one type of vocabulary requires learning four to five times (four and five days) with bad judgment and poor. However, after being given an action, then the average language skills of children with autism increased by only one or two lessons (one and two days) with the excellent score.